Uricase deficiency in rats results in a variety of metabolic disorders, addition to gouty nephropathy - Xulian Wan; Yu Yun; Shixiong Li; Guanyun Luo; Ning Li; Hua Yin; Weigang Duan (PLoS ONE, 2025)
Clinical evidence suggests that hyperuricemia is frequently associated with hyperglycemia (diabetes), hyperlipidemia, and hypertension. However, this relationship has not been fully verified in experimental animals. The present study used uricase-deficient rats (KDY rats, n = 125) with spontaneously elevated levels of serum uric acid (SUA) as the model animals and investigated their metabolic conditions throughout their lifespan (626 days of age). The serum, urine and feces of the rats were collected, histological examination was performed using hematoxylin-eosin or Masson’s staining, and gene expression was determined using transcriptome high-throughput sequencing. Compared with wild type (WT) rats of the same age, the SUA levels in KDY rats were continuously high (approximately 70 μg/mL), and the body weight gain slowed after 45 days of age, followed by increased urine output, diabetes mellitus (hyperglycemia), high low-density lipoprotein, and hypercholesterolemia. Histological examination showed that gouty nephropathy appeared after approximately 45 days of age, before the rats developed medullary injury, medullary interstitial fibrosis, cortical glomerulus injury, and glomerular fibrosis. KDY rats also showed signs of atherosclerosis and hypertension in the late stage of their lifespan. The lifespan of KDY rats was significantly shorter than that of WT rats (more than 626 days). The expected lifespan of KDY rats is approximately 450 days, and the direct cause of the shortened lifespan is renal failure caused by gout nephropathy. The direct mechanisms of the lesions in KDY are related to the upregulation of various of inflammatory (immune) pathways. In conclusion, it demonstrated that hyperuricemia in KDY rats leads to type 2 diabetes mellitus (hyperglycemia), hyperlipidemia, atherosclerosis, and hypertension, in addition to gouty nephropathy.